A Researching users' knowledge in the Field of Instant Messengers Security - Tsyliurnyk, Yevhenii; Tomenchuk, Oleksandr; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2023)
Nowadays, many people contact other people through various types of social networks and instant messaging. However, these platforms are often not a secure way to exchange information among people. In recent times, most people have started to pay attention to the level of security offered by communicators and the technologies used in them, which results in the emergence of communicators focused primarily on safe communication. However, the question arises: "Are user actions not negatively affecting security?" Do users consciously choose instant messaging? Do they use modern methods to protect accounts? The conducted study confirmed the relationship between the user's actions and the security of com-munication. Additionally, the aspects most influencing the choice of communicator were found.